Impacts of village isolation on childhood nutritional status in rural Malawi - Andrew J Claffey; Jennifer C George; Korinne A Thorne; Jon C Zelasko; Kyle W Zittel; David M Holmes (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background According to a recent 2018 survey, the rate of childhood acute malnutrition in Malawi has decreased while the rate of stunting in children under five has remained at 37.4%. Our study assesses the impact of child sex, child age, and household distance from main road access on nutritional status in rural Malawi. # Methods Anthropometric data was collected on a sample of children aged 0-18 years at three sites in rural Malawi. Z-scores were calculated based on normative height-for-weight and height-for-age World Health Organization (WHO) growth curves. Univariate odds ratios and 95% confidence intervals (CIs) were calculated for the association of the assessed risk factors with stunting prevalence. # Results 198 children were assessed \[46.4% male (92)\]. Children were grouped ages 0-<2 years (19, 10%), 2-<5 years (88, 44%), and 5- ≤18 years (91, 46%). 2.5% met criteria for wasting, 8.6% had moderate stunting, 5.1% had severe stunting. Data was collected from 3 villages at <2km (16%), 4-5km (35%) and >10 km (52%). Village distance of ≥10 km from the main road (OR = 2.91, CI = 1.26-6.75) and child age under 2 years (odds ratio, OR = 5.54, 95% CI = 1.61-19.1) were both significantly associated with childhood stunting. # Conclusions Within our sample, village distance ≥10 km from the main road and child age <2 years were both significantly associated with stunting. Our results suggest the need for greater resource access and allocation to isolated communities for future public health interventions.